An empirical study on the relationship between ownership and firm performance: Taiwan evidence. (28th January 2008) - Lin, Yu-Chih; Huang, Shaio Yan; Young, Shu-Chao
This study is to investigate the relationship between ownership and firm performance in the environment in which collateralising shares by directors and supervisors is a common practice. The sample includes firms that are listed on the Taiwan Stock Exchange from 1998 to 2002 except those in the financial industry. We find that a significant positive relationship (alignment) exists between ownership and firm performance (measured by ROA and ROE) when the net ownership is high. However, when the net ownership is low, the negative relationship (entrenchment) between ownership and performance is not significant. Besides, there is a significant negative relationship between collateralised shares of directors and supervisors and performance.